Kontestasi Politik dalam Pemilihan Kepala Desa di Desa Cambai Kecamatan Tulung Selapan Kabupaten OKI Sumatera Selatan Tahun 2021 - Diana Rizki; Amaliatulwalidain Amaliatulwalidain; Novia Kencana (Publikasi Indonesia, 2022)
The political contestation event in the Village Head Election which will be held on October 12, 2021, in Cambai Village, Tulung Selapan District, OKI Regency is a form of government authority for the village to regulate and manage the interests of its community following Law Number 6 of 2014 concerning Villages and strengthened by the PP of the Republic of Indonesia Number 72 of 2005 which involves the participation of rural communities in developing democratic life. The accumulation of capital owned by political contestants in the form of social capital, economic capital and political capital played a very important role in the contestants' success in winning the Cambai Village Head election. conflict and competition during the village head election. Method The research approach used is a descriptive approach Qualitative with the Inductive Sociology method, which is a method that departs from the existing socio-political realities and political events that appear on the surface to be analyzed comprehensively and linked to theories and concepts that have strong relevance. Conclusion: With his social capital strength, Syaipul Mesa managed to win this contest and could beat the political and economic capital ownership of other candidates for the Cambai Village Head, namely Zamharo and Alan Januar. The greater the accumulated capital owned by a candidate, the greater the support they will get from the village community.